Strategi Branding melalui Program Yaumul Qur’an sebagai Upaya Meningkatkan Kualitas Sekolah - Zaafarani Nabila Zahra; Mohamad Joko Susilo (An-Nuha, 2026)
This study examines the role of the Yaumul Qur’an Program as a branding strategy to enhance the quality and public image of SDIT Al-Fahmi. In the context of increasing competition among Islamic primary schools, educational branding is no longer limited to visual promotion but must be rooted in authentic educational practices. This research aims to analyze how Yaumul Qur’an contributes to institutional image building, students’ Qur’anic competence, and parental trust. Using a qualitative case study approach, data were collected through observation, in-depth interviews with school leaders and Qur’an coordinators, and documentation analysis. The findings reveal that the program strengthens students’ engagement with the Qur’an, improves memorization and recitation skills, and fosters positive parental perceptions toward the school. Moreover, Yaumul Qur’an functions as a value-based branding strategy that integrates religious habituation with institutional reputation. The study concludes that Qur’an-centered programs can serve as sustainable and distinctive branding strategies for Islamic educational institutions.